Rubber composition for tires

JP7640845B2Active Publication Date: 2025-03-06THE YOKOHAMA RUBBER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021069831
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-16
Publication Date
2025-03-06
Estimated Expiration
2041-04-16

AI Technical Summary

Benefits of technology

【0006】 本発明の発明者は、タイヤ用ゴム組成物に優れた氷上性能を付与するための配合剤について鋭意研究した結果、ポリウレタン系微粒子(特に、ヒドロキシ基を含む植物系脂肪酸エステル由来の合成物であり、その平均粒子径が1μm~100μmであるもの)を含む粒子分散体を用いることで、氷上性能およびウェット性能を向上し、更に良好な破断伸びを確保できることを知見した。本発明は、この知見に基づいて、タイヤ用ゴム組成物は上述の配合で構成し、粒子分散体の配合量や、粒子分散体中のポリウレタン系微粒子の割合を特定の範囲に設定しているので、氷上性能およびウェット性能を向上し、更に良好な破断伸びを確保し、これら性能をバランスよく高度に両立することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640845000001
    Figure 0007640845000001
  • Figure 0007640845000002
    Figure 0007640845000002
  • Figure 0007640845000003
    Figure 0007640845000003
Patent Text Reader

Abstract

To provide a rubber composition for tires capable of improving on-ice performance and wet performance and further securing good elongation at break.SOLUTION: The rubber composition for tires contains, based on 100 pts.mass of a diene rubber, 30-100 pts.mass of carbon black and / or a white filler and 0.1-30 pts.mass of a particle dispersion containing 10-60 mass% of polyurethane-based fine particles. The polyurethane-based fine particles used are a synthetic material derived from a vegetable fatty acid ester containing a hydroxy group and have an average particle diameter of 1-100 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition for tires intended to be used primarily in the tread portion of winter tires. [Background technology]

[0002] In a rubber composition used in the tread portion of a winter tire (e.g., a studless tire, etc.) that is expected to run on snowy and icy roads, it is required to improve the running performance (performance on ice) on snowy and icy roads. For example, Patent Document 1 proposes blending a powder obtained by crushing urethane foam into a rubber composition used in the tread portion of a studless tire. That is, since the powder of urethane foam maintains the elastic properties of the urethane foam, such as compression resistance and rebound elasticity, in the rubber composition, by dispersing it in the rubber, the elastic properties of the rubber composition are improved, and the flexibility of the rubber composition is ensured, thereby improving the ground contact with snowy and icy roads, thereby improving the performance on ice. In addition, since water generated by melting snow and ice may exist on snowy and icy roads, in addition to the above-mentioned performance, it is also required to further improve wet performance. In order to achieve both of these performance characteristics (performance on ice, wet performance, and breaking elongation), the incorporation of various materials into the rubber composition (such as urethane foam powder as proposed in the aforementioned Patent Document 1) has been considered. In particular, in recent years, from the perspective of environmental issues such as the depletion of petroleum resources and restrictions on carbon dioxide emissions, the use of naturally derived components has been considered. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-31521 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a rubber composition for tires which has improved performance on ice and on wet surfaces and which ensures good elongation at break. [Means for solving the problem]

[0005] The rubber composition for tires of the present invention which achieves the above object contains, for 100 parts by mass of diene rubber, carbon black and White Color filler In total The polyurethane-based fine particles are a synthetic product derived from a plant-based fatty acid ester containing a hydroxyl group, and have an average particle diameter of 1 μm to 100 μm. Effect of the Invention

[0006] The inventors of the present invention have conducted extensive research into compounding agents for imparting excellent performance on ice to rubber compositions for tires, and as a result have found that by using a particle dispersion containing polyurethane-based fine particles (particularly a synthetic product derived from a plant-based fatty acid ester containing a hydroxyl group and having an average particle size of 1 μm to 100 μm), it is possible to improve performance on ice and wet performance and ensure better elongation at break. Based on this finding, the rubber composition for tires in the present invention is constituted by the above-mentioned compounding, and the compounding amount of the particle dispersion and the ratio of the polyurethane-based fine particles in the particle dispersion are set within specific ranges, so that it is possible to improve performance on ice and wet performance, ensure better elongation at break, and achieve a high degree of compatibility between these performances in a well-balanced manner.

[0007] In the present invention, the particle dispersion is preferably a liquid diene polymer having a number average molecular weight of 1,000 to 100,000. The polyurethane fine particles are preferably surface-modified with a diene copolymer having an acid anhydride group or a carboxylic acid group. Furthermore, the vegetable fatty acid ester is preferably a castor oil polyol. This is advantageous in improving the performance on ice and wet performance and in securing good breaking elongation.

[0008] In the present invention, it is preferable that the diene rubber contains natural rubber and polybutadiene rubber, and the proportion of polybutadiene rubber in the diene rubber is 30 mass % or more. By using a diene rubber containing an appropriate amount of polybutadiene rubber in this way, the rubber physical properties become good, which is advantageous for improving performance on ice.

[0009] The rubber composition for tires of the present invention described above can be suitably used in the tread portion of a studless tire. A tire using the rubber composition for tires of the present invention in the tread portion can improve the performance on ice and on wet surfaces and ensure good elongation at break due to the excellent rubber properties described above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the rubber composition for tires of the present invention, the rubber component is a diene rubber. As the diene rubber, rubber generally used in rubber compositions for tires (particularly, rubber compositions for winter tires) can be used. In the present invention, it is particularly preferable that the diene rubber contains natural rubber and polybutadiene rubber. When the diene rubber contains natural rubber and polybutadiene rubber, the blending amount of the polybutadiene rubber is preferably 30% by mass or more, more preferably 30% by mass to 70% by mass in 100% by mass of the diene rubber. In addition, the blending amount of the natural rubber is preferably 30% by mass or more, more preferably 30% by mass to 70% by mass in 100% by mass of the diene rubber. If the blending amount of the polybutadiene rubber is less than 30% by mass, there is a risk of adversely affecting the flexibility at low temperatures. In addition, the rubber composition of the present invention can also contain diene rubber other than natural rubber and polybutadiene rubber. As the other diene rubber, rubber generally used in rubber compositions for tires, such as isoprene rubber and styrene-butadiene rubber, can be used. These other diene based rubbers may be used alone or in any blend.

[0011] The rubber composition of the present invention is compounded with 30 to 100 parts by mass, preferably 35 to 90 parts by mass, of carbon black and / or white filler per 100 parts by mass of diene rubber. By compounding an appropriate amount of carbon black or white filler in this way, the flexibility of the rubber composition can be ensured and the performance on ice can be improved. If the amount of carbon black and / or white filler is less than 30 parts by mass, the mechanical properties of the rubber composition cannot be sufficiently ensured, and basic tire performance (for example, hardness and abrasion resistance) may be reduced. If the amount of carbon black and / or white filler exceeds 100 parts by mass, the flexibility of the rubber composition decreases and it becomes difficult to ensure good performance on ice. When carbon black and white filler are used in combination, the above-mentioned compounding amount is the total amount of these two.

[0012] Examples of carbon black include furnace carbon blacks such as SAF, ISAF, HAF, FEF, GPF, HMF, and SRF, which may be used alone or in combination of two or more. The nitrogen adsorption specific surface area (N2SA) of carbon black is not particularly limited, but is preferably 40 m 2 / g~200m 2 / g, more preferably 50m 2 / g~150m 2 / g. The nitrogen adsorption specific surface area of ​​carbon black is preferably 40 m 2 By making the carbon black have a specific surface area of ​​200 m / g or more, the mechanical properties and abrasion resistance of the rubber composition can be ensured. 2 / g or less, good performance on ice can be achieved. In this specification, the nitrogen adsorption specific surface area N2SA of carbon black is measured in accordance with JIS K6217-2.

[0013] Examples of white fillers include silica, calcium carbonate, magnesium carbonate, talc, clay, alumina, aluminum hydroxide, titanium oxide, and calcium sulfate. These may be used alone or in combination of two or more. Among these, silica is preferred, as it can provide better performance on ice.

[0014] Examples of silica include wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), calcium silicate, aluminum silicate, etc., which may be used alone or in combination of two or more. The CTAB adsorption specific surface area of ​​silica is not particularly limited, but is preferably 80 m 2 / g~260m 2 / g, more preferably 140m 2 / g~200m 2 / g. The CTAB adsorption specific surface area of ​​silica is 80m 2 By making the CTAB adsorption specific surface area of ​​the silica 200 m / g or more, the abrasion resistance of the rubber composition can be ensured. 2 By making the CTAB specific surface area of ​​silica equal to or less than 1 / g, it is possible to improve wet performance and low rolling resistance. In this specification, the CTAB specific surface area of ​​silica is a value measured according to ISO 5794.

[0015] In the present invention, it is preferable to compound a silane coupling agent together with silica. By compounding a silane coupling agent, the dispersibility of silica in diene rubber can be improved, and the balance between wear resistance and performance on ice can be improved. The type of silane coupling agent is not particularly limited as long as it can be used in a rubber composition containing silica, and examples thereof include sulfur-containing silane coupling agents such as bis-(3-triethoxysilylpropyl) tetrasulfide, bis(3-triethoxysilylpropyl) disulfide, 3-trimethoxysilylpropyl benzothiazole tetrasulfide, γ-mercaptopropyl triethoxysilane, and 3-octanoylthiopropyl triethoxysilane. The amount of the silane coupling agent is preferably 3% by mass to 15% by mass, more preferably 5% by mass to 10% by mass, based on the weight of silica. If the amount of the silane coupling agent is less than 3% by mass of the amount of silica, there is a risk that the dispersion of silica cannot be sufficiently improved. If the amount of the silane coupling agent exceeds 15% by mass of the amount of silica, the silane coupling agent will condense with itself, making it impossible to obtain the desired hardness and strength in the rubber composition.

[0016] The rubber composition of the present invention is blended with a particle dispersion containing polyurethane-based fine particles as described below. As a result of extensive research into compounding agents for imparting excellent on-ice performance to rubber compositions for tires, the inventors of the present invention have found that by using a particle dispersion containing polyurethane-based fine particles having the properties described below, it is possible to improve on-ice performance and wet performance and ensure further good breaking elongation.

[0017] The polyurethane-based microparticles used in the present invention are synthetic products derived from plant-based fatty acid esters containing hydroxyl groups. Examples of plant-based fatty acid esters containing hydroxyl groups include castor oil-based polyols, palm oil-based polyols, and peanut oil-based polyols. Among these, castor oil-based polyols can be particularly preferably used. By containing the above-mentioned naturally derived polyurethane-based microparticles, the rubber composition can ensure appropriate flexibility and water absorption, which is advantageous for improving ice performance and wet performance while ensuring good breaking elongation. The term "polyurethane-based" refers to a compound having a bond such as a urea bond or a urethane bond that is generated by the reaction of an isocyanate group.

[0018] The polyurethane-based microparticles used in the present invention are preferably surface-modified with a diene-based copolymer having an acid anhydride group or a carboxylic acid group. By carrying out surface modification in this way, the number of double bonds in the molecule increases, crosslinking with rubber is improved, and the polyurethane-based microparticles can be prevented from falling off. Examples of diene-based copolymers having an acid anhydride group or a carboxylic acid group include maleic anhydride-modified polyisoprene, maleic anhydride-modified polybutadiene, and maleic anhydride-modified polystyrene butadiene.

[0019] The polyurethane-based microparticles used in the present invention have an average particle size of 1 μm to 100 μm, preferably 10 μm to 50 μm. Having such a suitable average particle size is advantageous for improving the performance on ice and wet performance, and for ensuring good breaking elongation. If the average particle size is less than 1 μm, there is no effect of improving friction on ice, and if the average particle size is more than 100 μm, the breaking elongation decreases.

[0020] As the particle dispersion used in the present invention, for example, a liquid diene-based polymer can be used. In particular, it is preferable that the polyurethane-based fine particles are compatible with the diene-based rubber that is the main component of the rubber composition of the present invention. In other words, it is preferable that the particle dispersion (liquid diene-based polymer) has a solubility parameter (SP value) close to that of the diene-based rubber that is the main component of the rubber composition of the present invention. In particular, it is preferable to use a liquid diene-based polymer that is composed of the same components as the diene-based rubber that is the main component of the rubber composition of the present invention.

[0021] When a liquid diene polymer is used as the particle dispersion, its number average molecular weight is preferably 1,000 to 100,000, more preferably 10,000 to 60,000. This is advantageous for improving ice performance and wet performance and ensuring better breaking elongation. If the number average molecular weight is less than 1,000, fine particles cannot be held, and the effect of improving friction on ice cannot be obtained. If the number average molecular weight exceeds 100,000, fine particles cannot be dispersed, and the effect of improving friction on ice decreases. Examples of liquid diene polymers having a number average molecular weight of 1,000 to 100,000 include liquid isoprene polymers, liquid butadiene polymers, and liquid styrene butadiene polymers.

[0022] In the present invention, the polyurethane-based microparticles are dispersed in the particle dispersion. The ratio of the polyurethane-based microparticles contained in the particle dispersion is 10% by mass to 60% by mass, preferably 20% by mass to 50% by mass. In this way, by making the particle dispersion contain an appropriate amount of polyurethane-based microparticles, it is advantageous to improve the performance on ice and wet performance and to ensure a good breaking elongation. If the ratio of the polyurethane-based microparticles contained in the particle dispersion is less than 10% by mass, the effect of improving friction on ice cannot be obtained. If the ratio of the polyurethane-based microparticles contained in the particle dispersion exceeds 60% by mass, the microparticles aggregate and the breaking properties decrease.

[0023] In the present invention, the above-mentioned particle dispersion containing the above-mentioned polyurethane-based fine particles is blended with the diene rubber, which is the main component of the rubber composition. In this case, the blending amount of the particle dispersion with respect to 100 parts by mass of the diene rubber is 0.1 parts by mass to 30 parts by mass, preferably 5 parts by mass to 20 parts by mass. Blending the particle dispersion in this manner is advantageous for improving the performance on ice and wet performance and ensuring better breaking elongation. If the blending amount of the particle dispersion is less than 0.1 parts by mass, the particle dispersion (polyurethane-based fine particles) is too small, so the effect of blending it cannot be fully obtained. If the blending amount of the particle dispersion exceeds 30 parts by mass, the breaking elongation of the rubber composition decreases.

[0024] The rubber composition for tires of the present invention may contain various additives that are generally used in rubber compositions for tires, such as vulcanizing or crosslinking agents, vulcanization accelerators, antioxidants, plasticizers, processing aids, liquid polymers, terpene resins, and thermosetting resins, within the range that does not impair the object of the present invention. These additives may be kneaded in a general manner to prepare a rubber composition, which can then be used for vulcanization or crosslinking. The amount of these additives may be a conventional amount, as long as it does not violate the object of the present invention. The rubber composition for tires may be produced by mixing the above-mentioned components using a general rubber kneading machine, such as a Banbury mixer, a kneader, or a roll.

[0025] The above-mentioned rubber composition for tires of the present invention can be suitably used in the tread portion of pneumatic tires (particularly winter tires such as studless tires expected to be driven on snowy and icy roads). A pneumatic tire using the rubber composition for tires of the present invention in the tread portion has excellent physical properties, which improves the ice performance, wet performance, and breaking elongation to levels higher than conventional levels, and can achieve a good balance between these performances.

[0026] The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to these examples. EXAMPLES

[0027] In preparing rubber compositions for tires (Standard Example 1, Comparative Examples 1-6, Examples 1-14) having the same compounding ingredients as shown in Table 3 and the compounding ingredients shown in Tables 1-2, the components except for sulfur and vulcanization accelerator were mixed in a 1.7 L Banbury mixer for 5 minutes, and when the temperature reached 145°C, the components were released to prepare masterbatches. Sulfur and vulcanization accelerator were added to the obtained masterbatches, and the mixture was mixed in an open roll at 70°C to obtain 21 types of rubber compositions for tires.

[0028] The obtained rubber compositions for tires were evaluated for wet performance, performance on ice, and elongation at break by the methods described below.

[0029] Wet Performance The obtained rubber composition for tires was vulcanized at 170°C for 10 minutes using a mold of a given shape (inner dimensions: length 150mm, width 150mm, thickness 2mm) to prepare a vulcanized rubber test piece. The dynamic viscoelasticity of the vulcanized rubber test piece was measured using a viscoelasticity spectrometer manufactured by Iwamoto Seisakusho Co., Ltd. under conditions of an elongation deformation strain rate of 10±2%, a vibration frequency of 20Hz, and a temperature of 0°C, and tan δ(0°C) was calculated. The obtained results are shown in the "Wet Performance" column of Tables 1 and 2 as an index with the value of Standard Example 1 set to 100. The larger this index, the larger the tan δ(0°C) and the better the wet grip performance.

[0030] On-ice performance The obtained rubber composition for tires was vulcanized at 170°C for 10 minutes using a mold of a given shape (inner dimensions: length 150 mm, width 150 mm, thickness 2 mm) to prepare a vulcanized rubber test piece. The vulcanized rubber test piece was attached to a flat cylindrical rubber base and tested using an inside drum type ice friction tester at a measurement temperature of -3.0°C and a load of 5.5 kg / cm. 2 The coefficient of friction on ice was measured under conditions of a drum rotation speed of 25 km / h. The results are shown in the "Performance on ice" column of Tables 1 and 2 as an index, with the value of Standard Example 1 being set at 100. The higher the index, the greater the frictional force on ice and the better the performance on ice. An index value of 105 or less means that the improvement in performance on ice is insufficient.

[0031] Breaking Elongation The obtained rubber composition for tires was vulcanized at 170°C for 10 minutes using a mold of a predetermined shape (inner dimensions: length 150 mm, width 150 mm, thickness 2 mm) to prepare a vulcanized rubber test piece. Using the vulcanized rubber test piece, a dumbbell JIS No. 3 test piece was prepared in accordance with JIS K6251, and a tensile test was performed at room temperature (20°C) at a tensile speed of 500 mm / min to measure the tensile breaking elongation when it broke. The obtained results are shown in the "breaking elongation" column of Tables 1 and 2 as an index with the value of Standard Example 1 set to 100. The larger the index value, the larger the tensile breaking elongation (the better the tensile properties). Note that if the index value is "110" or less, the effect of improving the breaking elongation is insufficient.

[0032] [Table 1]

[0033] [Table 2]

[0034] The types of raw materials used in Tables 1 and 2 are shown below. NR: Natural rubber, STR20 (glass transition temperature: -65°C) BR: Polybutadiene rubber, Zeon Nipol BR1220 (glass transition temperature: -110°C) CB: Carbon black, Cabot Japan's Show Black N339 Silica: Evonik Degussa ULTRASIL VN3 Silane coupling agent: Evonik Degussa Si69, bis(3-triethoxysilylpropyl)tetrasulfide Particle dispersions 1 to 9: Produced by the production method described below Urethane microparticles: Daimic Beads (average particle size: 200 μm) manufactured by Dainichiseika Chemicals Co., Ltd.

[0035] [Table 3]

[0036] The types of raw materials used in Table 3 are shown below. Zinc oxide: Three types of zinc oxide manufactured by Seido Chemical Stearic acid: Beads made by NOF Corporation, Stearic Acid YR Anti-aging agent: Amine-based anti-aging agent, Santoflex 6PPD manufactured by Flexis Wax: Paraffin wax manufactured by Ouchi Shinko Chemical Co., Ltd. Oil: Aroma oil, Showa Shell Sekiyu Extract No. 4S Sulfur: Hosoi Chemicals oil processing sulfur Vulcanization accelerator: Sulfenamide vulcanization accelerator, Sancerer CM-G manufactured by Sanshin Chemical Industry Co., Ltd.

[0037] Method for producing particle dispersion 1 55.0g of castor oil-based polyol A (HF-2009, manufactured by Ito Oil Mills, hydroxyl value 43.1mgKOH / g), 14.5g of dimethylthiotoluenediamine (Heartcure 30, manufactured by Kumiai Chemical Co., Ltd.), 79.5g of liquid isoprene polymer (LIR-30, manufactured by Kuraray Co., Ltd., number average molecular weight 28000), and 1.1g of sorbitan acid-based surfactant (TW-O320V, manufactured by Kao Co., Ltd.) were stirred for 2 minutes with a planetary centrifugal mixer. Next, 11.0g of polymeric MDI (Coronate 1331, manufactured by Tosoh Co., Ltd., NCO% 32.4%) was added and stirred for 2 minutes. Next, maleic anhydride-modified polyisoprene (LIR-403, manufactured by Kuraray Co., Ltd., number average molecular weight 34000, functional group number per molecule 3) was added to the mixture, and stirring was continued for 1 hour to obtain particle dispersion 1. The obtained particle dispersion 1 was measured by a laser diffraction particle size distribution analyzer, and it was confirmed that particles having an average particle size of 10 μm were produced. The content of particles contained in the particle dispersion 1 was 50 mass %.

[0038] Method for producing particle dispersion 2 40.0g of castor oil polyol A (HF-2009, manufactured by Ito Oil Milling Co., Ltd., hydroxyl value 43.1mgKOH / g) and 9.6g of 4,4'-diphenylmethane diisocyanate (Millionate MT, manufactured by Tosoh Corporation, number average molecular weight 250) were reacted at 80℃ for 5 hours to obtain a terminal isocyanate castor oil urethane prepolymer (a castor oil-based urethane prepolymer with isocyanate groups at the ends. It has urethane bonds.) 76.2g of liquid isoprene polymer (LIR-30, manufactured by Kuraray Co., Ltd., number average molecular weight 28000) and 1.2g of sorbitan acid surfactant (TW-O320V, manufactured by Kao Corporation) were added to the terminal isocyanate castor oil urethane prepolymer prepared as described above, and the mixture was stirred for 2 minutes with a planetary centrifugal mixer. Next, 2.0 g of dimethylthiotoluenediamine (Heartcure 30, Kumiai Chemical Co., Ltd.) and 7.4 g of polycarbonate diol (Duranol T5650J, Asahi Kasei Corporation, hydroxyl value 139.6 mgKOH / g) were added and stirred for 2 minutes. Next, 16.0 g of maleic anhydride-modified polyisoprene (LIR-403, Kuraray Co., Ltd., number average molecular weight 34000, number of functional groups per molecule 3) was added and stirred for 1 hour to obtain particle dispersion 2. When the obtained particle dispersion 2 was measured with a laser diffraction type particle size distribution measuring device, it was confirmed that particles with an average particle size of 30 μm were generated. In addition, the content of particles contained in particle dispersion 2 was 50 mass%.

[0039] Method for producing particle dispersion 3 Particle dispersion 3 was obtained according to the same procedure as in the "Manufacturing method of particle dispersion 1" described above, except that 50.0 g of castor oil-based polyol B (H-57 manufactured by Ito Oil Mills, hydroxyl value 92.9 mgKOH / g) was used instead of the above-mentioned castor oil-based polyol A, 2.2 g of dimethylthiotoluenediamine, 80.1 g of liquid isoprene polymer, 1.0 g of sorbitan acid surfactant, 16.9 g of polymeric MDI, and 10.0 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 3 was measured with a laser diffraction type particle size distribution measuring device, and it was confirmed that particles with an average particle size of 30 μm were generated. In addition, the content of particles contained in particle dispersion 3 was 50 mass%.

[0040] Method for producing particle dispersion 4 Particle dispersion 4 was obtained according to the same procedure as in the above-mentioned "Production method of particle dispersion 2", except that 30.0 g of castor oil-based polyol B (H-57 manufactured by Ito Oil Mills, hydroxyl value 92.9 mgKOH / g) was used instead of the above-mentioned castor oil-based polyol A, 18.6 g of 4,4'-diphenylmethane diisocyanate, 81.8 g of liquid isoprene polymer, 0.9 g of sorbitan acid surfactant, 4.3 g of dimethylthiotoluenediamine, 16.0 g of polycarbonate diol, and 12.0 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 4 was measured with a laser diffraction type particle size distribution measuring device, and it was confirmed that particles with an average particle size of 40 μm were generated. In addition, the content of particles contained in particle dispersion 4 was 50 mass%.

[0041] Method for producing particle dispersion 5 Particle dispersion 5 was obtained according to the same procedure as in the above-mentioned "Production method of particle dispersion 1", except that 37.0 g of castor oil-based polyol B (AC-009 manufactured by Ito Oil Mills, hydroxyl value 223.0 mgKOH / g) was used instead of the above-mentioned castor oil-based polyol A, 3.9 g of dimethylthiotoluenediamine, 79.0 g of liquid isoprene polymer, 0.7 g of sorbitan acid surfactant, 30.0 g of polymeric MDI, and 7.4 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 5 was measured with a laser diffraction type particle size distribution measuring device, and it was confirmed that particles with an average particle size of 30 μm were generated. In addition, the content of particles contained in particle dispersion 5 was 50 mass%.

[0042] Method for producing particle dispersion 6 Particle dispersion 6 was obtained according to the same procedure as in the above-mentioned "Production method of particle dispersion 2", except that 35.0 g of polycarbonate diol (Asahi Kasei Corporation's Duranol T4692, hydroxyl value 56.1 mgKOH / g) was used instead of the above-mentioned castor oil-based polyol A, 13.1 g of 4,4'-diphenylmethane diisocyanate, 77.4 g of liquid isoprene polymer, 1.1 g of sorbitan acid surfactant, 3.0 g of dimethylthiotoluenediamine, and 14.0 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 6 was measured with a laser diffraction particle size distribution measuring device, and it was confirmed that particles with an average particle size of 150 μm were generated. In addition, the content of particles contained in particle dispersion 6 was 50 mass%.

[0043] Method for producing particle dispersion 7 Particle dispersion 7 was obtained by the same procedure as in the "Production method of particle dispersion 1" described above, except that 11.0 g of the castor oil-based polyol A described above, 0.2 g of dimethylthiotoluenediamine, 138.3 g of liquid isoprene polymer, 0.2 g of sorbitan acid surfactant, 1.7 g of polymeric MDI, and 2.2 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 7 was measured with a laser diffraction particle size distribution measuring device, and it was confirmed that particles with an average particle size of 20 μm were generated. In addition, the content of particles contained in particle dispersion 7 was 10 mass%.

[0044] Method for producing particle dispersion 8 Particle dispersion 8 was obtained by the same procedure as in the "Production method of particle dispersion 1" described above, except that 33.0 g of the castor oil-based polyol A, 0.7 g of dimethylthiotoluenediamine, 107.6 g of liquid isoprene polymer, 0.7 g of sorbitan acid surfactant, 5.2 g of polymeric MDI, and 6.6 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 8 was measured with a laser diffraction particle size distribution measuring device, and it was confirmed that particles with an average particle size of 20 μm were generated. In addition, the content of particles contained in particle dispersion 8 was 30 mass%.

[0045] Method for producing particle dispersion 9 Particle dispersion 6 was obtained according to the same procedure as in the above-mentioned "Production method of particle dispersion 2", except that 33.0 g of polycarbonate diol (Duranol T5651 manufactured by Asahi Kasei Corporation, hydroxyl value 112 mgKOH / g) was used instead of the above-mentioned castor oil-based polyol A, 24.7 g of 4,4'-diphenylmethane diisocyanate, 88.7 g of liquid isoprene polymer, 0.9 g of sorbitan acid surfactant, 9.9 g of dimethylthiotoluenediamine, and 19.4 g of maleic anhydride-modified polyisoprene were used. The obtained particle dispersion 9 was measured with a laser diffraction type particle size distribution measuring device, and it was confirmed that particles with an average particle size of 50 μm were generated. In addition, the content of particles contained in particle dispersion 9 was 50 mass%.

[0046] Method for producing particle dispersion 10 Particle dispersion 10 was obtained according to the same procedure as in the "Production method of particle dispersion 1" described above, except that liquid isoprene polymer B (LIR-50 manufactured by Kuraray, number average molecular weight 54,000) was used instead of the liquid isoprene polymer A described above. The obtained particle dispersion 11 was measured with a laser diffraction type particle size distribution measuring device, and it was confirmed that particles with an average particle size of 50 μm were produced. In addition, the content of particles contained in particle dispersion 10 was 50 mass%.

[0047] As is clear from Table 1, the rubber compositions for tires of Examples 1 to 14 (using any one of Particle Dispersions 1 to 5, 7, 8, and 10) improved wet performance, ice performance, and breaking elongation compared to Standard Example 1, and achieved a high degree of compatibility between these. On the other hand, in Comparative Example 1 (using Particle Dispersion 6), the particles contained in the particle dispersion were not a synthetic product derived from a plant-based fatty acid ester containing a hydroxyl group, and the average particle diameter was too large, so the breaking elongation was deteriorated. In Comparative Example 2 (using Particle Dispersion 9), the particles contained in the particle dispersion were not a synthetic product derived from a plant-based fatty acid ester containing a hydroxyl group, so the ice performance and breaking elongation could not be sufficiently improved. In Comparative Example 3, since urethane fine particles were contained instead of a particle dispersion, the breaking elongation was deteriorated. In Comparative Example 4 (using Particle Dispersion 1), the amount of the particle dispersion was too large, so the breaking elongation was deteriorated. In Comparative Example 5 (using Particle Dispersion 1), the amount of silica and carbon black (total of fillers) was small, so the wet performance was deteriorated. In Comparative Example 6 (using Particle Dispersion 1), the blended amount (total of fillers) of silica and carbon black was large, and therefore the performance on ice and the elongation at break were reduced.

Claims

1. A rubber composition for tires, comprising 100 parts by mass of diene rubber, a total of 30 to 100 parts by mass of carbon black and a white filler, and 0.1 to 30 parts by mass of a particle dispersion containing 10 to 60% by mass of polyurethane fine particles, wherein the polyurethane fine particles are a synthetic product derived from a plant-based fatty acid ester containing a hydroxy group and have an average particle size of 1 μm to 100 μm.

2. 2. The rubber composition for tires according to claim 1, wherein the particle dispersion is a liquid diene-based polymer having a number average molecular weight of 1,000 to 100,000.

3. 3. The rubber composition for tires according to claim 1, wherein the polyurethane-based fine particles are surface-modified with a diene-based copolymer having an acid anhydride group or a carboxylic acid group.

4. 4. The rubber composition for a tire according to claim 1, wherein the vegetable fatty acid ester is a castor oil-based polyol.

5. 5. The rubber composition for tires according to claim 1, wherein the diene rubber contains natural rubber and polybutadiene rubber, and the proportion of the polybutadiene rubber in the diene rubber is 30 mass % or more.

6. A studless tire comprising a tread portion made of the rubber composition for tires according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for producing polyurethane beads

    JP2004107476A

  • JP2007‐31521A

  • Rubber composition for tire and studless winter tire

    JP2012211316A

  • Rubber composition for winter tire, and winter tire

    JP2014062168A

  • Polyurethane particle and method for producing the same

    JP2021155678A